Santo corpo profanado: escutas e performances na cultura afro-brasileira - Moraes, Bernadete Silveira (2009)
This study proposes to analyze the body in the processes of sanctification and profanation. Profanation, while constant in modern philosophical and scientific discourses, is a slow process which has strategically promoted a fragmentation in looking at the body. In practice, a de-ritualization. Sanctification, the continuous art of reintegrating the body at the centre of popular cultures, promotes an incessant reinvention of the body. Thus using tradition as a source in the modern day. Using a Cartographic methodological perspective, we have developed our research initially based on the observations and trajectories of the performances that seem to belong precisely to cultures which incorporate the body in their cultural manifestations. We have found in Carlinhos Brown and his musical group, a favorable example of these changes in both the local culture associated with tradition, and also in its global dimension